Preparation method and application of sulfonation catalyst for synthesizing methacrylonitrile

Through the preparation of sulfonation catalysts and electrostatic adsorption method, the by-product problem caused by the easy polymerization of methacrylonitrile is solved, and efficient methacrylonitrile production and catalyst regeneration are achieved, ensuring yield and catalyst stability.

CN119303595AActive Publication Date: 2025-01-14WUHUAN ENG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411332206.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

In the existing methacrylonitrile production process, methacrylonitrile is easily polymerized to form dimers, resulting in the by-products reducing the methacrylonitrile yield and covering the active sites of the catalyst in the ammonia oxidation reaction, which requires cumbersome regeneration treatment to restore activity. , resulting in the deactivation of the catalyst.

Method used

Using the sulfonation catalyst preparation method, a high-activity and stability sulfonation catalyst can be prepared by pickling and sulfonation treatment carriers, combined with electrostatic adsorption method, which can depolymethacreal dimer and be combined with ammonia source and oxygen. The source reaction was made to produce methacrylonitrile and catalyst regeneration was performed by simple filtration and drying.

Benefits of technology

The total conversion rate of methacrylonitrile and its dimer is greater than 98%, and the yield of methacrylonitrile can reach more than 95%. The catalyst can maintain activity through simple regeneration, avoiding side reactions covering the active site. The catalyst is deactivated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057291270000101
    Figure BDA0005057291270000101
  • Figure BDA0005057291270000111
    Figure BDA0005057291270000111
  • Figure BDA0005057291270000121
    Figure BDA0005057291270000121
Patent Text Reader

Abstract

The invention discloses a preparation method of a sulfonation catalyst for synthesizing methacrylonitrile, which comprises the following steps: adding carrier powder with large specific surface area into a beaker, and then adding an acid solution into the beaker; after uniformly stirring, carrying out suction filtration, washing and drying to obtain a carrier subjected to acid pickling treatment; adding the carrier subjected to acid pickling treatment into a hydrothermal kettle with a polytetrafluoroethylene lining, adding a sulfonation reagent and an organic reagent A, sealing the hydrothermal kettle, putting the hydrothermal kettle into a drying oven for treatment, and then performing suction filtration, washing and drying to obtain a carrier subjected to sulfonation treatment; weighing a manganese precursor and an auxiliary agent precursor, adding the manganese precursor and the auxiliary agent precursor into a beaker, adding an organic reagent B, magnetically stirring to fully dissolve, adding the sulfonated carrier into the beaker, stirring at room temperature, filtering, washing, drying, and finally roasting in a muffle furnace to obtain the sulfonation catalyst. Carrier vacancies are obtained through acid pickling, sulfonic acid groups, active elements and auxiliary elements can be effectively anchored, and the catalyst is good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic ammoxidation, and specifically relates to a preparation method and application of a sulfonation catalyst for synthesizing methacrylonitrile. Background Art

[0002] Methacrylonitrile is an important chemical raw material, currently mainly used to produce polymethacrylimide (PMI) foam, and to a certain extent, it is irreplaceable. As a high-performance polymer material, PMI foam has the characteristics of high specific strength, high specific modulus, high heat resistance, and high closed cell rate. It can be used as a structural core material in aerospace, rail transportation, medical equipment, wind power generation, radar antennas and other fields. The core product layout targets a market of over 50 billion yuan per year.

[0003] At present, the domestic PMI foam preparation technology has gradually matured, and its development is mainly restricted by the source of raw material methacrylonitrile. In recent years, domestic research institutes have conducted a lot of exploration on the production process of methacrylonitrile. Among them, the process of using methacrolein as raw material to prepare methacrylonitrile products by ammoxidation has the advantages of green environmental protection, low energy consumption, and few toxic byproducts. It is a potential industrial application route. However, the raw material methacrolein used in this process is a very active aldehyde. Even in the presence of an inhibitor, it is easy to dimerize to generate 3,4-dihydro-2,5-dimethyl-2H-pyran-2-carboxaldehyde (methacrolein dimer). For commercially available reagents, the purity of methacrolein is generally above 95% when leaving the factory, and the total mass fraction of methacrolein plus methacrolein dimer can reach more than 99%. After a period of storage, some methacrolein will polymerize to form methacrolein dimer. In severe cases, the mass fraction of methacrolein dimer in the reagent can reach more than 15%. When methacrolein containing dimers is used as a raw material, the dimers may react with ammonia and / or oxygen to generate corresponding by-products during the ammoxidation reaction. These by-products may reduce the final yield of methacrylonitrile and cover the active sites of the catalyst to poison the catalyst. In this case, the catalyst needs to be regenerated in a tedious manner to restore its activity. Otherwise, the accumulation of by-products may lead to the deactivation of the catalyst. Summary of the invention

[0004] The purpose of the present invention is to solve the above technical problems and provide a method for preparing a sulfonation catalyst for synthesizing methacrylonitrile with high activity and stability and its application.

[0005] To achieve the above object, the present invention provides a method for preparing a sulfonation catalyst for synthesizing methacrylonitrile, which is as follows:

[0006] 1) Preparation of acid-washed carrier

[0007] Add the large specific surface area carrier powder into a beaker, then add the acid solution into the beaker, and perform magnetic stirring in a water bath; after the stirring is completed, filter, wash, and dry to obtain the acid-washed carrier;

[0008] 2) Preparation of sulfonated carrier

[0009] The acid-washed carrier is added to a hydrothermal kettle with a polytetrafluoroethylene liner, a sulfonating agent and an organic reagent A are added, the hydrothermal kettle is sealed, and the hydrothermal kettle is placed in an oven for treatment, and then filtered, washed, and dried to obtain a sulfonated carrier;

[0010] 3) Preparation of sulfonation catalyst

[0011] Weigh the manganese precursor and the auxiliary agent precursor, add them into a beaker, add the organic reagent B, stir magnetically to fully dissolve, then add the sulfonated carrier into the beaker, stir at room temperature, filter, wash, dry, and finally place in a muffle furnace for calcination to obtain the sulfonated catalyst.

[0012] Furthermore, in the step 1), the mass ratio of the acid solution to the large specific surface area carrier powder is (20-80):1; the large specific surface area carrier powder is aluminum oxide, titanium dioxide or silicon dioxide carrier powder, and the specific surface area is 150-300m 2 / g; the acid solution is one or more of a nitric acid solution, a hydrochloric acid solution, and an acetic acid solution, and the concentration of the acid in the acid solution is 10 to 50 mmol / L.

[0013] Furthermore, in the step 1), the specific process of washing and drying is: washing the filter cake powder with ultrapure water until the conductivity of the filtrate is lower than 50 μS / cm; then washing the filter cake powder after washing with ultrapure water three times with an alcohol washing solution, and the amount of alcohol washing solution used each time is 5 to 20 times the mass of the filter cake powder after washing with ultrapure water; finally, placing the filter cake powder after alcohol washing in a vacuum oven and drying it at 40 to 80° C. under vacuum for 5 to 10 hours.

[0014] Furthermore, in the step 2), the mass ratio of the sulfonating agent to the organic agent A is 1:(100-300); the mass ratio of the pickled carrier to the sulfonating agent is determined according to the specific surface area of ​​the pickled carrier. When the specific surface area of ​​the pickled carrier is 150-200m 2 / g, the mass ratio of the acid-washed carrier to the sulfonating agent is (5-15):1; when the specific surface area of ​​the acid-washed carrier is 200-250m 2 / g, the mass ratio of the acid-washed carrier to the sulfonating agent is (3-12):1; when the specific surface area of ​​the acid-washed carrier is 250-300m 2 / g, the mass ratio of the acid-washed carrier to the sulfonating agent is (2-10):1.

[0015] The sulfonating agent is one of chlorosulfonic acid and aminosulfonic acid; the organic reagent A is one or more of anhydrous methanol, anhydrous ethanol, acetone, acetonitrile, tetrahydrofuran, N,N-dimethylformamide, thionyl chloride, carbon tetrachloride, chloroform, pyridine and pyrrole.

[0016] Furthermore, in the step 1), the water bath temperature is 40-80° C.; in the step 2), the hydrothermal kettle is placed in an oven and treated at a temperature of 110-150° C. for 10-24 hours.

[0017] Furthermore, in the step 2), the specific process of washing and drying is: wash the filter cake powder three times with an alcohol washing solution, each time using an alcohol washing solution of 5 to 20 times the mass of the filter cake powder, put it in a vacuum oven, and dry it at 40 to 80° C. under vacuum for 5 to 10 hours.

[0018] Furthermore, in the step 3), the molar ratio of the manganese precursor to the auxiliary agent precursor is (1-10):1; the mass ratio of the manganese precursor to the organic reagent B is 1:(1000-5000), and the mass fraction of manganese in the sulfonation catalyst is 0.5-2.5%, and the mass fraction of the auxiliary agent element is 0.06-3.0%.

[0019] The manganese precursor is one or more of anhydrous manganese acetate, manganese acetylacetonate, and bis(cyclopentadienyl)manganese; the auxiliary agent precursor is one or more of a copper auxiliary agent precursor and a zinc auxiliary agent precursor, wherein the copper auxiliary agent precursor is one or more of copper acetylacetonate, copper glycinate, copper citrate, copper acetylacetate, and copper oxalate; the zinc auxiliary agent precursor is one or more of anhydrous zinc acetate, zinc isopropoxide, zinc acrylate, zinc propionate, and zinc glycinate; and the organic reagent B is one or more of anhydrous methanol, anhydrous ethanol, acetonitrile, tetrahydrofuran, acetylacetone, pyridine, and pyrrole.

[0020] Furthermore, in the step 3), the specific process of washing and drying is: washing the filter cake powder three times with an alcohol washing solution, each time using an alcohol washing solution of 5 to 20 times the mass of the filter cake powder, placing it in a vacuum oven, and drying it at 40 to 80° C. under vacuum for 5 to 10 hours; and calcining it at 250 to 400° C. in a muffle furnace for 2 to 10 hours.

[0021] In the step 3), the alcohol washing liquid is one or more of anhydrous methanol, anhydrous ethanol, anhydrous ethylene glycol, anhydrous glycerol, and anhydrous propylene glycol.

[0022] Also provided is an application of the sulfonation catalyst as described above, wherein the sulfonation catalyst is used to prepare methacrylonitrile using methacrolein containing dimers as a raw material;

[0023] The reaction is a slurry bed reaction, in which a sulfonation catalyst, a methacrolein raw material containing a dimer and an organic reagent C are added to a reactor, ammonia gas is introduced into the system as an ammonia source, oxygen gas is introduced into the system as an oxygen source, and an ammoxidation reaction is carried out under stirring to prepare methacrylonitrile; at the same time, for the methacrolein dimer present in the raw material, the sulfonation catalyst can first depolymerize it into a methacrolein monomer, and then an ammoxidation reaction is carried out with the ammonia source and the oxygen source to generate the target product methacrylonitrile, the total conversion rate of methacrolein and its dimer is greater than 98%, the methacrylonitrile yield can reach more than 95%, and the catalyst can be regenerated by a simple filtering and drying method, and the activity is not significantly reduced after 10 applications.

[0024] The mass ratio of the sulfonation catalyst, the methacrolein containing dimers, and the organic reagent C is 1: (6-20): (50-100); the molar ratio of the methacrolein containing dimers (the dimers are converted into methacrolein), ammonia, and oxygen is 1: (0.5-10): (0.5-10).

[0025] The reaction pressure is 2-6 MPa, the temperature is 30-70° C., and the reaction time is 2-30 min.

[0026] Furthermore, the organic reagent C is one or more of acetonitrile, tetrahydrofuran, dimethyl sulfoxide, toluene, ethyl acetate, and butyl acetate.

[0027] The catalyst carrier disclosed in the present invention is selected from a catalyst having a large specific surface area (≥150m 2 / g) of aluminum oxide, titanium dioxide or silicon dioxide carrier, the carrier is in powder form, commercial products or homemade products can be used, and the large specific surface area carrier can provide more vacancies after acid washing, which is convenient for the subsequent loading of sulfonic acid groups, active components and auxiliary agents. First, a certain concentration of dilute acid is used to treat the carrier. On the one hand, some impurities on the surface of the carrier can be removed, such as sodium, potassium and other elements remaining in the preparation process, and carbonates, hydroxyls, etc. formed by adsorbing small molecules in the air. On the other hand, evenly distributed vacancies can be formed, which is convenient for the subsequent loading of sulfonic acid groups, active components and auxiliary agents; in this process, the concentration of dilute acid needs to be strictly controlled. If the concentration is too high, the carrier will be over-etched, resulting in carrier waste. If the concentration is too low, the surface of the carrier will not be completely removed, and the number of vacancies is insufficient. Subsequently, the carrier is subjected to sulfonation treatment, and the carrier, sulfonating agent and solvent are placed in a hydrothermal kettle for solvent thermal reaction. The carrier obtained by acid washing in the previous step can be sulfonated, and the sulfonic acid groups on the obtained carrier are evenly distributed. By controlling the ratio of the carrier to the sulfonating agent, the surface density of the sulfonic acid groups on the carrier can be effectively controlled. If the surface density of the sulfonic acid groups is too low, the number of depolymerization active sites for catalytic dimer depolymerization will be insufficient, and methacrolein dimers will remain during the ammoxidation reaction, resulting in side reactions and covering the catalyst active sites. If the surface density of the sulfonic acid groups is too high, the carrier will have insufficient vacancies when the subsequent active components and auxiliary agents are loaded, and some of them cannot be effectively loaded or the loading position is unstable. Aggregation of active components and auxiliary agents is likely to occur during the reaction, resulting in decreased activity. Finally, the active manganese component and auxiliary element are adsorbed onto the vacancies of the carrier after sulfonation by electrostatic adsorption, and the sulfonated catalyst is obtained by drying and calcining. Thanks to the electrical properties of the sulfonic acid group, the active components and auxiliary agents electrostatically adsorbed onto the carrier are preferentially filled into the vacancies obtained by acid washing around the sulfonic acid group. During the reaction, these active elements and auxiliary agent elements are stable in nature and are not prone to migration and aggregation. At the same time, during the reaction, the sulfonic acid group can catalyze the depolymerization of methacrolein dimers, and the resulting monomer methacrolein can quickly migrate to the adjacent active sites to undergo an ammoxidation reaction to produce methacrylonitrile. This process fully utilizes the dimers in the raw materials and reduces the occurrence of side reactions. In addition, during the entire catalyst preparation process, except for the first step of washing with dilute acid, in which the water contained in the dilute acid inevitably contacts the carrier, and the subsequent washing with anhydrous organic reagents to remove water, the reagents and washing reagents in the remaining steps all use anhydrous reagents, which effectively avoids the formation of hydroxyl groups on the catalyst surface and can further reduce the occurrence of side reactions. At the same time, low-temperature drying in a vacuum oven is used to prevent the migration and aggregation of effective components.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1) The carrier used in the sulfonation catalyst prepared by the present invention is a conventional carrier, which can be a commercial sample or prepared by itself, with low cost. The reagents used for subsequent pickling and sulfonation are also conventional reagents with low price. The preparation method is simple and easy, which is convenient for industrial production;

[0030] 2) The present invention obtains carrier vacancies through acid washing, which can effectively anchor the sulfonic acid groups and the active elements and auxiliary elements. The catalyst has good stability and can be regenerated by simple filtering and drying. The experiment was applied 10 times and the activity did not decrease significantly.

[0031] 3) The sulfonic acid group can catalyze the depolymerization of methacrolein dimer into methacrolein monomer. At the same time, thanks to the electrical properties of the sulfonic acid group, the active elements and auxiliary elements are loaded around the sulfonic acid group, which is convenient for the series occurrence of the two reactions of dimer depolymerization and methacrolein ammoxidation, and the methacrolein dimer in the raw material can be fully utilized. The total conversion rate of methacrolein and its dimer is greater than 98%, and the yield of methacrylonitrile can reach more than 95%. At the same time, it can effectively avoid the side reaction of the dimer to cover the active site and cause the catalyst to deactivate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the gas chromatogram of the methacrolein raw material used in Experimental Example 1. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific embodiments.

[0034] Example 1

[0035] Preparation of 2.50wt%Mn2.89wt%Cu / Al2O3 Catalyst

[0036] Weigh 30g of industrial large specific surface area (216m 2 / g) aluminum oxide powder is added into a beaker, and then 600g of a prepared dilute hydrochloric acid solution with a concentration of 45mmol / L is added. The mixture is magnetically stirred for 15h in a water bath at 45°C, filtered, and the filter cake powder is washed with ultrapure water until the filtrate conductivity is lower than 50μS / cm (the final filtrate conductivity is measured to be 43μS / cm). The filter cake powder is then washed three times with anhydrous methanol, with 200g of anhydrous methanol used each time. The mixture is placed in a vacuum oven and dried at 40°C under vacuum for 6h to obtain an acid-washed carrier.

[0037] Weigh 25 g of the acid-washed carrier (the measured specific surface area after acid washing is 225 m 2 / g), added into a hydrothermal kettle with a polytetrafluoroethylene liner, added with 5g chlorosulfonic acid and 600g anhydrous methanol, sealed the hydrothermal kettle, put into an oven, treated at 115°C for 20h, filtered, and the filter cake powder was washed three times with anhydrous methanol, each time with 180g anhydrous methanol, put into a vacuum oven, and dried at 40°C for 6h under vacuum to obtain a sulfonated carrier.

[0038] Weigh 1.664g of anhydrous manganese acetate and 2.517g of copper acetylacetonate, add to a beaker, add 1664g of acetylacetone, stir magnetically to fully dissolve, add 20g of sulfonated carrier to the beaker, stir at room temperature for 30h, filter, wash the filter cake powder three times with anhydrous methanol, each time using 150g of anhydrous methanol, put it in a vacuum oven, dry it at 40°C under vacuum for 6h, finally put the sample in a muffle furnace and calcine at 250°C for 5h to obtain a 2.50wt% Mn2.89wt% Cu / Al2O3 sulfonated catalyst.

[0039] Example 2

[0040] Preparation of 1.00wt%Mn0.39wt%Cu / TiO2 Catalyst

[0041] Weigh 50g of self-made large specific surface area (183m 2 / g) titanium dioxide powder is added into a beaker, and then 3000g of a prepared dilute nitric acid solution with a concentration of 18mmol / L is added. The mixture is magnetically stirred for 20h in a water bath at 50°C, filtered, and the filter cake powder is washed with ultrapure water until the filtrate conductivity is lower than 50μS / cm (the final measured filtrate conductivity is 45μS / cm). The filter cake powder is then washed three times with anhydrous ethanol, with 500g of anhydrous ethanol used each time. The mixture is placed in a vacuum oven and dried at 55°C under vacuum for 6h to obtain an acid-washed carrier.

[0042] Weigh 20 g of the acid-washed carrier (the measured specific surface area after acid washing is 194 m 2 / g), added into a hydrothermal autoclave with a polytetrafluoroethylene liner, added with 2.0g chlorosulfonic acid and 400g anhydrous ethanol, sealed the hydrothermal autoclave, put into an oven, treated at 130°C for 15h, filtered, and the filter cake powder was washed three times with anhydrous ethanol, each time with 200g anhydrous ethanol, put into a vacuum oven, and dried at 55°C for 6h under vacuum to obtain a sulfonated carrier.

[0043] Weigh 0.547g of bis(cyclopentadienyl)manganese and 0.211g of copper glycinate, add to a beaker, add 1641g of pyridine, stir magnetically to fully dissolve, add 16g of sulfonated carrier to the beaker, stir at room temperature for 15h, filter, wash the filter cake powder three times with anhydrous ethanol, each time using 150g of anhydrous ethanol, put it in a vacuum oven, dry it at 55°C under vacuum for 6h, finally put the sample in a muffle furnace and calcine at 350°C for 8h to obtain a 1.00wt% Mn0.39wt% Cu / TiO2 sulfonated catalyst.

[0044] Example 3

[0045] Preparation of 0.50wt%Mn0.06wt%Zn / SiO2 Catalyst

[0046] Weigh 20g of industrial large specific surface area (264m 2 / g) silica powder is added into a beaker, and then 1600g of a prepared dilute acetic acid solution with a concentration of 11mmol / L is added, and the mixture is magnetically stirred for 17h in a water bath at 80°C, and filtered, and the filter cake powder is washed with ultrapure water until the filtrate conductivity is lower than 50μS / cm (the final measured filtrate conductivity is 36μS / cm), and then the filter cake powder is washed three times with anhydrous ethylene glycol, each time using 300g of anhydrous ethylene glycol, and placed in a vacuum oven, and dried at 80°C under vacuum for 10h to obtain an acid-washed carrier.

[0047] Weigh 15 g of the acid-washed carrier (the measured specific surface area after acid washing is 293 m 2 / g), added into a hydrothermal autoclave with a polytetrafluoroethylene liner, added with 3.0g of aminosulfonic acid and 800g of pyridine, sealed the hydrothermal autoclave, put into an oven, treated at 150°C for 20h, filtered, and the filter cake powder was washed three times with anhydrous ethylene glycol, each time with 220g of anhydrous ethanol, put into a vacuum oven, and dried at 80°C for 10h under vacuum to obtain a sulfonated carrier.

[0048] Weigh 0.322g of manganese acetylacetonate and 0.0115g of zinc isopropoxide, add to a beaker, add 1288g of tetrahydrofuran, stir magnetically to fully dissolve, add 10g of sulfonated carrier to the beaker, stir at room temperature for 36h, filter, wash the filter cake powder three times with anhydrous ethylene glycol, each time using 150g of anhydrous ethanol, put it in a vacuum oven, dry it at 80°C under vacuum for 10h, finally put the sample in a muffle furnace and calcine at 400°C for 7h to obtain a 0.50wt% Mn0.06wt% Zn / SiO2 sulfonated catalyst.

[0049] Example 4

[0050] 1.00wt%Mn0.29wt%Cu0.30%Zn / TiO2 Catalyst Preparation

[0051] Weigh 50g of self-made large specific surface area (183m 2 / g) titanium dioxide powder is added into a beaker, and then 3000g of a prepared dilute nitric acid solution with a concentration of 18mmol / L is added. The mixture is magnetically stirred for 20h in a water bath at 50°C, filtered, and the filter cake powder is washed with ultrapure water until the filtrate conductivity is lower than 50μS / cm (the final measured filtrate conductivity is 45μS / cm). The filter cake powder is then washed three times with anhydrous ethanol, with 500g of anhydrous ethanol used each time. The mixture is placed in a vacuum oven and dried at 55°C under vacuum for 6h to obtain an acid-washed carrier.

[0052] Weigh 20 g of the acid-washed carrier (the measured specific surface area after acid washing is 194 m 2 / g), added into a hydrothermal autoclave with a polytetrafluoroethylene liner, added with 2.0g chlorosulfonic acid and 400g anhydrous ethanol, sealed the hydrothermal autoclave, put into an oven, treated at 130°C for 15h, filtered, and the filter cake powder was washed three times with anhydrous ethanol, each time with 200g anhydrous ethanol, put into a vacuum oven, and dried at 55°C for 6h under vacuum to obtain a sulfonated carrier.

[0053] Weigh 1.042g of manganese acetylacetonate, 0.194g of copper acetylacetonate and 0.0929g of zinc isopropoxide, add to a beaker, add 2605g of acetonitrile, stir magnetically to fully dissolve, add 16g of sulfonated carrier to the beaker, stir at room temperature for 18h, filter, wash the filter cake powder three times with anhydrous ethanol, each time using 150g of anhydrous ethanol, put it in a vacuum oven, dry it at 55°C under vacuum for 6h, finally put the sample in a muffle furnace and calcine at 300°C for 5h to obtain 1.00wt%Mn0.29wt%Cu0.30%Zn / TiO2 sulfonated catalyst.

[0054] Comparative Example 1

[0055] Preparation of 1.00wt%Mn0.39wt%Cu / TiO2-unwashed-sulfonated catalyst

[0056] Directly use the un-acid-washed self-made large specific surface area (183m 2 / g) titanium dioxide powder was used as a catalyst carrier. The sulfonation treatment and the loading of active components and auxiliary agents were consistent with those in Example 2.

[0057] Weigh 20g of self-made large specific surface area (183m 2 / g) titanium dioxide powder, add it into a hydrothermal kettle with a polytetrafluoroethylene liner, add 2.0g chlorosulfonic acid and 400g anhydrous ethanol, seal the hydrothermal kettle, put it into an oven, treat it at 130°C for 15h, filter it, wash the filter cake powder three times with anhydrous ethanol, each time using 200g of anhydrous ethanol, put it into a vacuum oven, and dry it at 55°C under vacuum for 6h to obtain a sulfonated carrier.

[0058] Weigh 0.547g of bis(cyclopentadienyl)manganese and 0.211g of copper glycinate, add to a beaker, add 1641g of pyridine, stir magnetically to fully dissolve, add 16g of sulfonated carrier to the beaker, stir at room temperature for 15h, filter, wash the filter cake powder three times with anhydrous ethanol, each time using 150g of anhydrous ethanol, put it in a vacuum oven, dry it at 55°C under vacuum for 6h, finally put the sample in a muffle furnace and calcine at 350°C for 8h to obtain a 1.00wt%Mn0.39wt%Cu / TiO2-unacid-sulfonated catalyst.

[0059] Comparative Example 2

[0060] Preparation of 1.00wt%Mn0.39wt%Cu / TiO2-acid-washed-unsulfonated catalyst

[0061] Acid-washed self-made titanium dioxide powder with a large specific surface area was used as a catalyst preparation carrier. The active component and the auxiliary agent were directly loaded without sulfonation treatment, which was consistent with Example 2.

[0062] Weigh 50g of self-made large specific surface area (183m 2 / g) titanium dioxide powder is added into a beaker, and then 3000g of a prepared dilute nitric acid solution with a concentration of 18mmol / L is added. The mixture is magnetically stirred for 20h in a water bath at 50°C, filtered, and the filter cake powder is washed with ultrapure water until the filtrate conductivity is lower than 50μS / cm (the final measured filtrate conductivity is 45μS / cm). The filter cake powder is then washed three times with anhydrous ethanol, with 500g of anhydrous ethanol used each time. The mixture is placed in a vacuum oven and dried at 55°C under vacuum for 6h to obtain an acid-washed carrier.

[0063] Weigh 0.547g of bis(cyclopentadienyl)manganese and 0.211g of copper glycinate, add to a beaker, add 1641g of pyridine, stir magnetically to fully dissolve, add 16g of the acid-washed carrier to the beaker, stir at room temperature for 15h, filter, wash the filter cake powder three times with anhydrous ethanol, each time using 150g of anhydrous ethanol, put it in a vacuum oven, dry it at 55°C under vacuum for 6h, finally put the sample in a muffle furnace and calcine at 350°C for 8h to obtain a 1.00wt% Mn0.39wt% Cu / TiO2-acid-unsulfonated catalyst.

[0064] Experimental Example 1: The catalysts prepared in the above examples and comparative examples were used to catalyze the ammoxidation of methacrolein and dimer to prepare methacrylonitrile.

[0065] The sulfonated catalysts prepared in Examples 1 to 4 were used as a comparison with the catalysts prepared in Comparative Examples 1 to 2 to examine the performance of the catalysts in a slurry bed reactor in catalyzing the ammoxidation of methacrolein containing dimers as a raw material to prepare methacrylonitrile. At the same time, the ammoxidation regeneration stability of the catalysts prepared in Example 2 and Comparative Examples 1 to 2 was examined.

[0066] 1g of catalyst, 10g of methacrolein raw material containing dimer and 70g of tetrahydrofuran solvent were added to the slurry bed reactor respectively, the reactor was sealed, 3.5g of ammonia and 3MPa of air (oxygen content of about 6.5g) were charged, the temperature was turned on to 50°C, mechanical stirring was turned on, and the reaction was carried out for 15min. After the reaction was completed, the temperature was lowered and the gas was slowly released to normal pressure, the reactor was opened, and the obtained solution was subjected to chromatographic analysis to analyze the total conversion rate of methacrolein and dimer, the selectivity and yield of methacrylonitrile.

[0067] like Figure 1 As shown, the mass fraction of methacrolein in the methacrolein raw material containing dimers is 82.3%, and the mass fraction of methacrolein dimers is 16.9%, and the ammoxidation reaction conversion rate and methacrylonitrile selectivity and yield are calculated based on this.

[0068] As shown in Table 1, the sulfonated catalysts prepared by the present invention all exhibit excellent ammoxidation catalytic activity, the total conversion rate of methacrolein and its dimer is above 98%, and the yield of methacrylonitrile can reach up to 95.8%. In contrast, the catalysts prepared in Comparative Examples 1 to 2, 1.00wt%Mn0.39wt%Cu / TiO2-unpickling-sulfonated catalyst and 1.00wt%Mn0.39wt%Cu / TiO2-pickling-unsulfonated catalyst, have lower ammoxidation activity. For the 1.00wt%Mn0.39wt%Cu / TiO2-unwashed-sulfonated catalyst, since it was not acid-washed, impurities existed on the carrier and there was insufficient vacancies, resulting in limited loading of sulfonic acid groups, which restricted its performance in depolymerizing methacrolein dimers. However, some dimers could react with ammonia sources and / or oxidation, so the total conversion rate of methacrolein and its dimers (93.6%) was higher than the conversion rate of methacrolein only when it was completely converted (83.0%). In addition, due to insufficient vacancies, the active components and auxiliary agents were not completely loaded or the loading position was unstable, and some side reactions occurred, resulting in a low yield of methacrylonitrile (75.2%). For the 1.00wt%Mn0.39wt%Cu / TiO2-acid-unsulfonated catalyst, since no sulfonation treatment was performed, the methacrolein dimer could not be depolymerized. Although the dimer in the raw material could react with the ammonia source and / or oxidation, it was difficult to generate the target product methacrylonitrile, resulting in a low methacrylonitrile yield (79.1%).

[0069] Table 1

[0070]

[0071] A cyclic regeneration experiment was conducted on the 1.00wt%Mn0.39wt%Cu / TiO2 sulfonated catalyst prepared in Example 2, the 1.00wt%Mn0.39wt%Cu / TiO2-unpickled-sulfonated catalyst prepared in Comparative Example 1, and the 1.00wt%Mn0.39wt%Cu / TiO2-pickled-unsulfonated catalyst prepared in Comparative Example 2. The regeneration method was to filter the solution after the reaction, and directly put the obtained filter cake into an oven at 110°C and dry it for 10 hours to obtain a regenerated catalyst, and the ammonia oxidation activity of the regenerated catalyst was evaluated according to the previous ratio.

[0072] As shown in Table 2, the 1.00wt%Mn0.39wt%Cu / TiO2 sulfonated catalyst prepared in Example 2 of the present invention has no obvious decline in ammonia oxidation activity after simple regeneration. After ten regeneration experiments, the total conversion rate of methacrolein and its dimer can still be maintained at more than 98%, and the methacrylonitrile yield is maintained at about 95%. As a comparison, the 1.00wt%Mn0.39wt%Cu / TiO2-unpickling-sulfonated catalyst prepared in Comparative Example 1 has poor initial activity. After one regeneration, the reaction activity decreases rapidly. After the second regeneration, the methacrylonitrile yield has dropped to a very low level, and the catalyst is deactivated. The reason for the analysis is that the catalyst is not pickled, impurities exist on the carrier, and there is insufficient vacancy, resulting in limited sulfonic acid groups and active components and auxiliary agent loading, causing some side reactions to occur and covering some active sites. At the same time, during the reaction and regeneration process, some active components and auxiliary agent loading positions are unstable, and the force acting on the carrier is small, so migration and aggregation occur, further reducing the methacrylonitrile yield. The 1.00wt%Mn0.39wt%Cu / TiO2-acid-washed-unsulfonated catalyst prepared in Comparative Example 2 has poor initial activity. After one regeneration, the reaction activity decreases. After three regenerations, the methacrylonitrile yield drops to below 50%. Since the catalyst is not sulfonated, the methacrolein dimer cannot be depolymerized. During the reaction, the dimer can react with the ammonia source and / or oxidation. The by-products will cover the active sites and gradually accumulate during multiple reactions, causing the catalyst to gradually deactivate.

[0073] Table 2

[0074]

[0075]

Claims

1. A method for preparing a sulfonation catalyst for synthesizing methacrylonitrile, characterized in that: The preparation method shown is as follows: 1) Preparation of acid-washed carrier Add the large specific surface area carrier powder into a beaker, then add the acid solution into the beaker, and perform magnetic stirring in a water bath; after the stirring is completed, filter, wash, and dry to obtain the acid-washed carrier; 2) Preparation of sulfonated carrier The acid-washed carrier is added to a hydrothermal kettle with a polytetrafluoroethylene liner, a sulfonating agent and an organic reagent A are added, the hydrothermal kettle is sealed, and the hydrothermal kettle is placed in an oven for treatment, and then filtered, washed, and dried to obtain a sulfonated carrier; 3) Preparation of sulfonation catalyst Weigh the manganese precursor and the auxiliary agent precursor, add them into a beaker, add the organic reagent B, stir magnetically to fully dissolve, then add the sulfonated carrier into the beaker, stir at room temperature, filter, wash, dry, and finally place in a muffle furnace for calcination to obtain the sulfonated catalyst.

2. The method for preparing a sulfonation catalyst for synthesizing methacrylonitrile according to claim 1, characterized in that: In the step 1), the mass ratio of the acid solution to the large specific surface area carrier powder is (20-80):1; the large specific surface area carrier powder is aluminum oxide, titanium dioxide or silicon dioxide carrier powder, and the specific surface area is 150-300m 2 / g; the acid solution is one or more of a nitric acid solution, a hydrochloric acid solution, and an acetic acid solution, and the concentration of the acid in the acid solution is 10 to 50 mmol / L.

3. The method for preparing a sulfonation catalyst for synthesizing methacrylonitrile according to claim 1, characterized in that: In the step 1), the specific process of washing and drying is: washing the filter cake powder with ultrapure water until the conductivity of the filtrate is lower than 50 μS / cm; then washing the filter cake powder washed with ultrapure water three times with an alcohol washing solution, and the amount of alcohol washing solution used each time is 5 to 20 times the mass of the filter cake powder washed with ultrapure water; finally, placing the filter cake powder washed with alcohol in a vacuum oven and drying it at 40 to 80° C. under vacuum for 5 to 10 hours.

4. The method for preparing a sulfonation catalyst for synthesizing methacrylonitrile according to claim 1, characterized in that: In the step 2), the mass ratio of the sulfonating agent to the organic agent A is 1:(100-300); when the specific surface area of ​​the acid-washed carrier is 150-200m 2 / g, the mass ratio of the acid-washed carrier to the sulfonating agent is (5-15):1; when the specific surface area of ​​the acid-washed carrier is 200-250m 2 / g, the mass ratio of the acid-washed carrier to the sulfonating agent is (3-12):1; when the specific surface area of ​​the acid-washed carrier is 250-300m 2 / g, the mass ratio of the acid-washed carrier to the sulfonating agent is (2-10):1; The sulfonating agent is one of chlorosulfonic acid and aminosulfonic acid; the organic reagent A is one or more of anhydrous methanol, anhydrous ethanol, acetone, acetonitrile, tetrahydrofuran, N,N-dimethylformamide, thionyl chloride, carbon tetrachloride, chloroform, pyridine and pyrrole.

5. The method for preparing a sulfonation catalyst for synthesizing methacrylonitrile according to claim 1, characterized in that: In the step 1), the water bath temperature is 40-80° C.; in the step 2), the hydrothermal kettle is placed in an oven and treated at a temperature of 110-150° C. for 10-24 hours.

6. The method for preparing a sulfonation catalyst for synthesizing methacrylonitrile according to claim 1, characterized in that: In the step 2), the specific process of washing and drying is: wash the filter cake powder three times with an alcohol washing solution, each time using an alcohol washing solution of 5 to 20 times the mass of the filter cake powder, put it in a vacuum oven, and dry it at 40 to 80° C. under vacuum for 5 to 10 hours.

7. The method for preparing a sulfonation catalyst for synthesizing methacrylonitrile according to claim 1, characterized in that: In the step 3), the molar ratio of the manganese precursor to the auxiliary agent precursor is (1-10):1; the mass ratio of the manganese precursor to the organic reagent B is 1:(1000-5000), and the mass fraction of manganese in the sulfonation catalyst is 0.5-2.5%, and the mass fraction of the auxiliary agent element is 0.06-3.0%; The manganese precursor is one or more of anhydrous manganese acetate, manganese acetylacetonate, and bis(cyclopentadienyl)manganese; the auxiliary agent precursor is one or more of a copper auxiliary agent precursor and a zinc auxiliary agent precursor, wherein the copper auxiliary agent precursor is one or more of copper acetylacetonate, copper glycinate, copper citrate, copper acetylacetate, and copper oxalate; the zinc auxiliary agent precursor is one or more of anhydrous zinc acetate, zinc isopropoxide, zinc acrylate, zinc propionate, and zinc glycinate; and the organic reagent B is one or more of anhydrous methanol, anhydrous ethanol, acetonitrile, tetrahydrofuran, acetylacetone, pyridine, and pyrrole.

8. The method for preparing a sulfonation catalyst for synthesizing methacrylonitrile according to claim 1, characterized in that: In the step 3), the specific process of washing and drying is: wash the filter cake powder three times with an alcohol washing solution, each time using an alcohol washing solution of 5 to 20 times the mass of the filter cake powder, put it in a vacuum oven, dry it at 40 to 80° C. under vacuum for 5 to 10 hours; and calcine it at 250 to 400° C. in a muffle furnace for 2 to 10 hours.

9. An application of the sulfonation catalyst as claimed in claim 1, characterized in that: The sulfonation catalyst is used to prepare methacrylonitrile using methacrolein containing dimers as raw materials; The reaction is a slurry bed reaction, in which a sulfonation catalyst, a methacrolein raw material containing dimers and an organic reagent C are added to a reactor, ammonia gas as an ammonia source and oxygen gas as an oxygen source are introduced into the system, and an ammoxidation reaction is carried out under stirring to prepare methacrylonitrile; The mass ratio of the sulfonation catalyst, the methacrolein containing dimers, and the organic reagent C is 1: (6-20): (50-100); the molar ratio of the methacrolein containing dimers (the dimers are converted into methacrolein), ammonia, and oxygen is 1: (0.5-10): (0.5-10); The reaction pressure is 2-6 MPa, the temperature is 30-70° C., and the reaction time is 2-30 min.

10. The use of the sulfonation catalyst according to claim 9, characterized in that: The organic reagent C is one or more of acetonitrile, tetrahydrofuran, dimethyl sulfoxide, toluene, ethyl acetate, and butyl acetate.

Citation Information

Patent Citations

  • Sulfonic functionalized mesoporous silicon dioxide microsphere loaded metal oxide catalyst and preparation method and application of catalyst

    CN104646033A

  • Manganese-based catalyst for synthesizing methacrylonitrile and preparation and application of manganese-based catalyst

    CN109772298A

  • Sulfonic acid modified carrier loaded solid acid catalyst and preparation method and application thereof

    CN112121817A

  • Monatomic catalyst for synthesizing methacrylonitrile and preparation method thereof

    CN115970677A

  • High-activity and high-stability catalyst for synthesizing methacrylonitrile as well as preparation method and application thereof

    CN117732466A